2012
DOI: 10.1186/2110-5820-2-s1-s20
|View full text |Cite
|
Sign up to set email alerts
|

Renal replacement therapy with net fluid removal lowers intra-abdominal pressure and volumetric indices in critically ill patients

Abstract: BackgroundLittle is known about the effects of renal replacement therapy (RRT) with fluid removal on intra-abdominal pressure (IAP). The global end-diastolic volume index (GEDVI) and extravascular lung water index (EVLWI) can easily be measured bedside by transpulmonary thermodilution (TPTD). The aim of this study is to evaluate the changes in IAP, GEDVI and EVLWI in critically ill patients receiving slow extended daily dialysis (SLEDD) or continuous venovenous haemofiltration (CVVH) with the intention of net … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 39 publications
2
8
0
Order By: Relevance
“…On the one hand, our findings confirm results from our previous study and are also in accordance with a recently published retrospective cohort analysis : EVLWI was found to be elevated before hemodialysis, indicating excess pulmonary fluid, and a significant reduction was observed with fluid removal on dialysis. In contrast, the preload parameter ITBVI remained unchanged.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…On the one hand, our findings confirm results from our previous study and are also in accordance with a recently published retrospective cohort analysis : EVLWI was found to be elevated before hemodialysis, indicating excess pulmonary fluid, and a significant reduction was observed with fluid removal on dialysis. In contrast, the preload parameter ITBVI remained unchanged.…”
Section: Discussionsupporting
confidence: 93%
“…According to another study, extracorporal circulation during RRT per se did not lead to biased volumetric hemodynamic measurements . In a small pilot study published in 2007, we reported significant decreases in EVLW with fluid removal on intermittent hemodialysis in critically ill patients—a finding that was recently confirmed in a study by De Laet and co‐workers with an equivalently small sample size of nine patients . The present study was conducted to reassess and report potential changes in volumetric hemodynamic measurements with fluid removal on hemodialysis in a larger group of 35 ICU patients with ARF.…”
supporting
confidence: 72%
“…Renal replacement therapy with ultrafiltration has also been shown to decrease IAP . The indications for diuresis and renal replacement therapy are not established, but this may reduce cumulative fluid balance and IAP.…”
Section: Nonsurgicalmentioning
confidence: 99%
“…43 Renal replacement therapy with ultrafiltration has also been shown to decrease IAP. 44 The indications for diuresis and renal replacement therapy are not established, but this may reduce cumulative fluid balance and IAP. These strategies should be performed cautiously once the patient has been stabilized from the initial insult to avoid precipitating intravascular hypovolemia and hemodynamic instability.…”
Section: Optimize Fluid Administrationmentioning
confidence: 99%
“…De laet et al demonstrated similarly that RRT with a mean net fluid loss of 1.9 L in a total of 25 dialysis sessions decreased IAP from 12 to 11 mm Hg (P < 0.0001) [35]. Finally, Dabrowski et al recently concluded that continuous RRT to reduce fluid overload in patients with septic shock and acute kidney injury reduces IAP [36].…”
Section: Place For Furosemide Infusion or Renal Replacement Therapymentioning
confidence: 91%